THE EFFECT OF ANTIBACTERIA POWER ALBUMIN EGG ON SPECIES BACTERIA SALMONELLLA SP - Permata Ika Hidayati; Tri Ida Wahyu Kustyorini (Jurnal Sains Peternakan, 2016)
The aims of This to analyze power obstruent antibacterial on eggs albumin of various types of poultry against some species the bacterium Salmonella sp. The research is experimental explorative with a variable in the form of albumin the egg various types of poultry. Bound in the from variable zone obstruent the growth of bacteria Salmonella sp. Testing done with the methods diffusion that. Testing the antibacterial albumin eggs of various types of poultry is performed by measuring diameter obstruent colonies zone growth each species of the bacteria. Salmonella sp on medium nutrients that. Research conducted obtained from the measurement result in diameter zone obstruent species the bacteria Salmonella sp. Research in analysis using analysis single, and followed by test duncan 5%. The result of research showed that in albumin eggs poultry are power obstruent antibacterial and the obstruent stringest owned by albumin chicken egg. It was because albumin chicken having lysozyme that high compared with egg albumin poultry which other. According to statistical analyses said that the antibacterial albumin egg give the difference (P